Bespoke Crowdfunding Regulation: A Boost up to Startups and SMEs in India - Nikam, Rahul J. (Hasanuddin University, 2019)
The paper reviews securities regulatory requirements across the world and specifically in India that may be applicable or prohibiting Crowdfunding in India. The author argues that Indian financial and securities services regulations were not designed keeping in mind the 21st century requirements of industry. There is a regulatory gap in recognizing this emerging route of fund-raising business model addressing the needs of start-up as well as the Small and Medium Enterprises (SMEs) businesses by way of crowdfunding and cross-border crowdfunding in the form of equity and debt. Thus, paper is seeking to clarify how crowdfunding fits into existing rules if any and necessity of introducing specific requirements that promote regulatory and supervisory convergence. The aim is to provide appropriate balance of less costly regulatory compliances, prudent risks management for project owners and crowdfunding platforms vis-à-vis raising of funds domestically and through cross-broader. At the same time providing adequate investor protection to the investor who are typically not professional investors.